2011
DOI: 10.1038/ejcn.2011.161
|View full text |Cite
|
Sign up to set email alerts
|

Risk of metabolic syndrome in adults exposed to the great Chinese famine during the fetal life and early childhood

Abstract: Background/Objectives: To determine whether exposure to the Chinese famine during fetal life and early childhood was associated with a greater risk of metabolic syndrome in later life. Subjects/Methods: We used data of adults from the 2008 annual physical examinations in Public Health Center of the First Affiliated Hospital of Chongqing Medical University in Chongqing. To minimize misclassification of the famine exposure periods, subjects born in 1959 and 1962 were excluded. Totally, 5040 participants were enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
61
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 37 publications
11
61
0
Order By: Relevance
“…These results indicate that the hepatic cholesterol metabolism of female offspring may be easily affected by PEE. This finding is similar to the results of several epidemiological studies, with the most classic cases being those of the Netherland and Chinese famines [40, 41]. The intrauterine nutrition restriction caused by the famine involved in the studies was similar to PEE, and all of these adverse prenatal environments could lead to IUGR, with female more easily developing lipid accumulation and obesity.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These results indicate that the hepatic cholesterol metabolism of female offspring may be easily affected by PEE. This finding is similar to the results of several epidemiological studies, with the most classic cases being those of the Netherland and Chinese famines [40, 41]. The intrauterine nutrition restriction caused by the famine involved in the studies was similar to PEE, and all of these adverse prenatal environments could lead to IUGR, with female more easily developing lipid accumulation and obesity.…”
Section: Discussionsupporting
confidence: 79%
“…The intrauterine nutrition restriction caused by the famine involved in the studies was similar to PEE, and all of these adverse prenatal environments could lead to IUGR, with female more easily developing lipid accumulation and obesity. Particularly, the survival of adult female with metabolic syndrome exposed to the Chinese famine in their early lives was significantly higher than that of adult males [40]. It is likely that an adverse intrauterine environment is better able to affect the neuroendocrine programming of lipid metabolic-related genes of female foetuses in utero .…”
Section: Discussionmentioning
confidence: 99%
“…Although the evidence is conflicting, it may be that the detrimental effects of the Dutch famine extended into the following generation, with the offspring of women born in the famine found to have a lower birth weight [161,181]. Similar associations between early-life famine exposure and subsequent elevated chronic disease risk were reported following the Biafran conflict of 1968 to 1970 [182], and the Chinese famine of 1959 to 1961 [183][184][185][186]. In the latter, early-life exposure was also associated with increased risk of schizophrenia [187,188].…”
Section: Intergenerational Associationssupporting
confidence: 49%
“…It is a catastrophe in human history, but now it is a valuable chance to investigate the relationship between famine exposure and MS in Chinese. In China, just two studies examined this association and revealed a significant association between famine exposure during fetus and infancy and higher risk of MS in adulthood [13,14], though the only study based on Dutch Famine found no significant association [15]. In these studies, they used ATP III [16] and Chinese Diabetes Society criteria [14].…”
Section: Introductionmentioning
confidence: 98%